Gender Quotas or Girls' Networks? Evidence from an Italian Research Selection - Daniele Checchi; Simona Cicognani; Nevena Kulic (Institute of Labor Economics (IZA), 2018)
This article investigates the role of the gender composition of selection committees and the role of connections in promoting women in research activities. Exploiting a newly collected data set on recruitment processes to entry-level research positions in a leading Italian research centre operating mainly in the hard sciences, the study finds that bias against women manifests itself at non-tenured entry level and is attenuated by the presence of a woman on the selection committee. However, the most important predictor for recruitment in the study is previous connections with the research centre, a mechanism which, due the lower density of network links with the institute among female candidates, operates as a selection device discriminating against women. The results suggest that gender of the committee members, network structure and type of recruitment must all be taken into account in approaching recruitment policy and that very early stages of scientific careers are crucial for addressing gender bias in research.
Keywords: J70; 330; Italy; gender quotas; gender bias; connections; research recruitment